REALITAS MODERASI BERAGAMA DALAM UCAPAN HARI BESAR KEAGAMAAN - Arifin, Sultonul (Moderatio: Jurnal Moderasi Beragama, 2022)
In understanding Christmas greetings, it must be understood holistically and integrally on the one hand but on the other hand it must also be separate. Confusion and misunderstanding will result in wrong actions and so on. So that the considerations used do not always start from the text and must also end in the text again. However, it must be viewed from various sources and existing approaches so as to produce a complete conclusion. By dividing the two concepts above, namely the concept of theology (shari>'ah) and tolerance above, differences will appear and conflicts that will arise are relatively avoidable.